Loss of canonical Wnt signaling is involved in the pathogenesis of Alzheimer's disease - Tapia-Rojas, Cheril; Inestrosa, Nibaldo C. (My University, 2018)
Alzheimer's disease (AD) is the most common form of dementia in the older population, however, the precise cause of the disease is unknown. The neuropathology is characterized by the presence of aggregates formed by amyloid-beta (A beta) peptide and phosphorylated tau; which is accompanied by progressive impairment of memory. Diverse signaling pathways are linked to AD, and among these the Wnt signaling pathway is becoming increasingly relevant, since it plays essential roles in the adult brain. Initially, Wnt signaling activation was proposed as a neuroprotective mechanism against A beta toxicity. Later, it was reported that it participates in tau phosphorylation and processes of learning and memory. Interestingly, in the last years we demonstrated that Wnt signaling is fundamental in amyloid precursor protein (APP) processing and that Wnt dysfunction results in A beta production and aggregation in vitro. Recent in vivo studies reported that loss of canonical Wnt signaling exacerbates amyloid deposition in a transgenic (Tg) mouse model of AD. Finally, we showed that inhibition of Wnt signaling in a Tg mouse previously at the appearance of AD signs, resulted in memory loss, tau phosphorylation and A beta formation and aggregation; indicating that Wnt dysfunction accelerated the onset of AD. More importantly, Wnt signaling loss promoted cognitive impairment, tau phosphorylation and A beta(1-42) production in the hippocampus of wild-type (WT) mice, contributing to the development of an Alzheimer's-like neurophatology. Therefore, in this review we highlight the importance of Wnt/beta-catenin signaling dysfunction in the onset of AD and propose that the loss of canonical Wnt signaling is a triggering factor of AD.
Keywords: wnt signaling; wnt target genes; wnt/beta-catenin; alzheimer disease; amyloid-beta; tau phosphorylation; memory loss; synaptic dysfunction